WORKSHOP : OPTIMIZING EARLY CHILDREN'S BRAIN DEVELOPMENT THROUGH CREATIVE LEARNING MODELS AND MEDIA IN THE INFEPENDENT CURRICULUM - Iis Novianti; Debie Susanti; Dian Anggraeni; Istiqomah; Firga Sudarsi; Indri Rahmawati; Tety Srihayati; Abdul Haris (International Conferences on Early Childhood Education Proceedings, 2023)
The purpose of implementing community service activities in the form of workshops is for students to be able to utilize the knowledge gained from the results of studying at the university, as well as changes in knowledge and improvement of teaching in the world of education from the target group. The research was conducted using a qualitative descriptive approach. The data used is based on tests of 50 workshop participants. The results of the initial analysis show that there are PAUD teachers in Lemah Abang and Karawang Timur Sub-Districts who do not yet have insight into how stimulation optimizes brain development as well as various learning styles or models in early childhood. Based on the results of the pre-test, only 4% or 2 participants had an understanding in the very good category while 54% or 27 participants were still in the poor category, 18% or 9 participants were in the good category and the remaining 24% or 12 people were in the good category. After the implementation of this workshop activity, the results of the post-test showed an increase in workshop participants having a very good understanding. This is evidenced by the participants who scored in the range of 81 to 100 as many as 84% ​​or 42 participants, while the remaining 16% or 8 participants were in the good category. With this workshop activity, teachers are able to increase their knowledge capacity, especially about optimizing early childhood brain development through creative learning models and media.